Partially randomized, non-blinded trial of DNA and MVA therapeutic vaccines based on hepatitis B virus surface protein for chronic HBV infection. - James S Cavenaugh; Dorka Awi; Maimuna Mendy; Adrian V S Hill; Hilton Whittle; Samuel J McConkey (PLoS ONE)
Background Chronic HBV infects 350 million people causing cancer and liver failure. We aimed to assess the safety and efficacy of plasmid DNA (pSG2.HBs) vaccine, followed by recombinant modified vaccinia virus Ankara (MVA.HBs), encoding the surface antigen of HBV as therapy for chronic HBV. A secondary goal was to characterize the immune responses. Methods Firstly 32 HBV e antigen negative (eAg(-)) participants were randomly assigned to one of four groups: to receive vaccines alone, lamivudine (3TC) alone, both, or neither. Later 16 eAg(+) volunteers in two groups received either 3TC alone or both 3TC and vaccines. Finally, 12 eAg(-) and 12 eAg(+) subjects were enrolled into higher-dose treatment groups. Healthy but chronically HBV-infected males between the ages of 15-25 who lived in the western part of The Gambia were eligible. Participants in some groups received 1 mg or 2 mg of pSG2.HBs intramuscularly twice followed by 5×10(7) pfu or 1.5×10(8) pfu of MVA.HBs intradermally at 3-weekly intervals with or without concomitant 3TC for 11-14 weeks. Intradermal rabies vaccine was administered to a negative control group. Safety was assessed clinically and biochemically. The primary measure of efficacy was a quantitative PCR assay of plasma HBV. Immunity was assessed by IFN-γ ELISpot and intracellular cytokine staining. Results Mild local and systemic adverse events were observed following the vaccines. A small shiny scar was observed in some cases after MVA.HBs. There were no significant changes in AST or ALT. HBeAg was lost in one participant in the higher-dose group. As expected, the 3TC therapy reduced viraemia levels during therapy, but the prime-boost vaccine regimen did not reduce the viraemia. The immune responses were variable. The majority of IFN-γ was made by antigen non-specific CD16(+) cells (both CD3(+) and CD3(-)). Conclusions The vaccines were well tolerated but did not control HBV infection. Trial registration ISRCTN ISRCTN67270384.